Dissecting and modeling the emergent murine TEC compartment during ontogeny. Issue 7 (22nd May 2017) - Brunk, Fabian; Michel, Chloé; Holland‐Letz, Tim; Slynko, Alla; Kopp‐Schneider, Annette; Kyewski, Bruno; Pinto, Sheena
Abstract : Using a combination of ex vivo analysis, Re‐aggregate Thymic Organ Culture (RTOC) reconstitution assays and mathematical modeling, we traced emergent lineage commitment in murine embryonic TECs. Our data support the following developmental sequence: MHCII neg TECs → MHCII lo TECs → cTECs → MHCII hi TECs, wherein the emergent cTECs directly generate mature MHCII hi mTECs, thus supporting the asynchronous model of TEC lineage commitment. Abstract : The origin of the thymic epithelium, i.e. the cortical (cTEC) and medullary (mTEC) epithelial cells, from bipotent stem cells through TEC progenitors and lineage‐specific progeny still remains poorly understood. We sought to obtain an unbiased view of the incipient emergence of TEC subsets by following embryonic TEC development based on co‐expression of EpCAM, CD80 and MHC class II (MHCII) on non‐hematopoietic (CD45 − ) thymic stromal cells in wild‐type BL6 mice. Using a combination of ex vivo analysis, Re‐aggregate Thymic Organ Culture (RTOC) reconstitution assays and mathematical modeling, we traced emergent lineage commitment in murine embryonic TECs. Both experimental and mathematical datasets supported the following developmental sequence: MHCII − CD80 − → MHCII lo CD80 − → MHCII hi CD80 − → MHCII hi CD80 hi TECs, whereby MHCII hi CD80 − and MHCII hi CD80 hi TECs bear features of cTECs and mTECs respectively. These emergent MHCII hi CD80 − cTECs directly generate mature MHCII hi CD80 hi mTECs in vivo and in vitro, thus supporting the asynchronous model of TEC lineage commitment.